Corrosion Behavior of CoCrFeMnNi High-Entropy Alloys (HEAs) Under Aqueous Acidic Conditions. (7th July 2017) - Rodriguez, Alvaro; Tylczak, Joseph H; Ziomek-Moroz, Margaret
Abstract : The corrosion behavior of high-entropy alloys (HEAs) from the CoCrFeMnNi family was evaluated in CO2 containing 3.5 weight percent sodium chloride (NaCl) at pH 4 and temperature of 40°C by electrochemical and immersion methods. Their corrosion parameters were compared to those of Hastelloy® C276 (UNS N10276) and stainless steel 316L (UNS 31600). Corrosion rates were determined by weight loss analysis and corrosion current methods for each of the alloys. During immersion testing experiments, HEA-1 (high Cr content) had the lowest corrosion rate and HEA-8 (no Cr content) underwent metal dissolution and exhibited the highest corrosion rate. On the other hand, after potentiodynamic polarization measurements, significant pitting corrosion was developed on the surface of all the alloys except HEA-8 and C276, where scanning electron microscopy (SEM) analyses depicted general corrosion. HEA-6 exhibited the lowest corrosion rate while HEA-2 had the highest. Scanning electron microscopy (SEM) analyses of the corroded surfaces after electrochemical testing revealed that HEA-8 underwent general corrosion while the rest of HEAs and stainless steel 316L underwent pitting corrosion. X-ray diffraction (XRD) on immersion testing samples revealed the presence of oxide-rich phases in formed corrosion products of HEA-8.